2017
DOI: 10.7860/jcdr/2017/21778.9298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidants ( β -mercaptoethanol and Cysteamine) on Assisted Reproductive Technology In vitro

Abstract: IntrOductIOnIVM of oocytes is an effective method for the production of mature oocyte used in ART, which includes IVF cloning and Intra Cytoplasmic Sperm Injection (ICSI). IVM is a cost-benefit technique with few side effects for gonadotropin stimulation of IVF, and is a simple treatment for certain infertile couple [1][2][3][4]. The GV-stage oocytes which are stripped of cumulus cells have a reduced developmental capacity when compared with cumulus enclosed GV-stage oocytes [5,6]. Cumulus cells play an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…GSH plays central roles in oocyte maturation and in protecting them from damages reactive oxygen species-induced [80]. In a mouse model, in vitro maturation (IVM) of immature oocytes and IVF outcome resulted favored by the concomitant supplementation of 100 µM β-mercaptoethanol and cysteamine in culture media [80]. These findings are in line with the results obtained using a bovine in vitro system [81].…”
Section: Coenzime Q10supporting
confidence: 83%
See 1 more Smart Citation
“…GSH plays central roles in oocyte maturation and in protecting them from damages reactive oxygen species-induced [80]. In a mouse model, in vitro maturation (IVM) of immature oocytes and IVF outcome resulted favored by the concomitant supplementation of 100 µM β-mercaptoethanol and cysteamine in culture media [80]. These findings are in line with the results obtained using a bovine in vitro system [81].…”
Section: Coenzime Q10supporting
confidence: 83%
“…β-mercaptoethanol and cysteamine are thiol compounds that stimulate GSH synthesis. GSH plays central roles in oocyte maturation and in protecting them from damages reactive oxygen species-induced [ 80 ]. In a mouse model, in vitro maturation (IVM) of immature oocytes and IVF outcome resulted favored by the concomitant supplementation of 100 µM β-mercaptoethanol and cysteamine in culture media [ 80 ].…”
Section: Agents Consideredmentioning
confidence: 99%
“…The positive effects of antioxidants on IVM and embryo development has been widely reported, such as the quality of porcine blastocysts during in vitro embryonic development can be markedly improved by the addition of β‐mercaptoethanol (BME) and l ‐ascorbic acid (AC) (Castillo‐Martin et al, 2014). The rate of IVM and oocyte evolution, and murine embryo formation could be significantly increased by the addition of BME and cysteamine (CYS)(Nikseresht et al, 2017). Moreover, the combination of resveratrol and melatonin supported a synergistic increase in oocyte nuclear maturation and total cell numbers of PA blastocysts and improved the development of somatic cell nuclear transfer (SCNT) embryos (Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports showed that over 1% DMSO has cellular toxic effect through alterations in the structure of plasma membrane, cytoplasm [29,30], extrusion of 1PB [29], dysregulated gene expression and apoptosis [7]. In turn, blastocyst rate in 1% DMSO was similar to control group and it showed a quadratic response with an optimum at 0.45% v:v. This response is probably due a long-term effect of maturation on oocyte developmental since part of oocyte competence is acquired during this complex and dynamic process [32,33,34,35,36,37,38,39]. On the other hand, when similar doses of DMSO were used for a longer period, during the in vitro culture, effect on blastocyst rates was not observed [40,6].…”
Section: Revisedmentioning
confidence: 99%